PENTINGNYA MEMAHAMI PERKEMBANGAN PESERTA DIDIK BAGI GURU DAN CALON GURU SEKOLAH DASAR - Shofia Ani; Eka Anggraini Siagian; Hanny Nabila Humairah; Herdika Fauzan Ginting; Sri Wahyuni (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Specially in elementary schools. Education is an important factor in developing students' potential, and the success of educational programs in formal schools is influenced by students, teaching staff, curriculum, infrastructure and environment. Education personnel must have academic qualifications, competence, educational certificates, be physically and spiritually healthy, and have the determination to realize national education. This research uses research that focuses on the approach model for study content, discussion and information collected through print media and technology. It also focuses on library research or literature review. The results and discussion explain that understanding student development can help teachers choose the best learning environment and get to know their students' personalities better. There are two benefits in understanding student development: for educators, it provides a general overview of how humans or individuals develop throughout their lives and the factors that influence that development. And for students, it provides a general overview of how learning procedures are suitable for the child's developmental stage.